Optimization of strawberry disinfection by fogging of a mixture of peracetic acid and hydrogen peroxide based on microbial reduction, color and phytochemicals retention - Van de Velde, Franco (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2016)
© The Author(s) 2016.